Numerical method for solving the inverse problem of oil reservoir development under elastic water drive conditions - Gamzaev, Khanlar Mekhvali (Computational Continuum Mechanics, 2012)
The inverse problem of determining boundary conditions in the oil well gallery from the prescribed law of motion for liquid-liquid interface under elastic water drive conditions is considered. The algorithm for solving the obtained system of equations is based on the method of rectifying the fronts and the difference method.
Keywords: difference method; method of rectifying the fronts; inverse boundary value problem; elastic water drive mode; oil reservoir